Test and Analysis of Characteristics of Safe Driving Speed on Typical Ice-snow Road. (June 2020) - Meng, Enjie; Wang, Bing; Wei, Ji'ao; Liu, Haoran; Zhao, Kuo; Hu, Ze
Abstract: When a motor vehicle driver encounters ice-snow road on low-grade road, it is easy to cause traffic incidents or even accidents because it is difficult to autonomously control the safe speed, which is a hot and difficult problem in the cold areas of northern China; At present, there is little research on the characteristics of safe driving speed on different types of ice-snow roads at home and abroad. In this paper, six types of typical ice-snow roads, such as fresh snow, snowboards, semi-melted snowboards, ice boards, semi-melted snowboards, and "black ice" (snow-covered ice), were constructed to test the safe driving speed and its corresponding main factors, and the data was processed to explore the safe driving speed on different types of ice-snow roads and its relationship with the main influencing factors; this study has practical significance for guiding drivers to autonomously control safe vehicle speed on ice-snow road, and also provides reference for the development of intelligent transportation technologies such as speed guidance, dynamic speed limit and autonomous driving.